Penguatan Kapasitas UMKM Tenun Ikat Giri Putri melalui Pemasaran Digital dan Pencatatan Keuangan Berbasis Aplikasi - Ni Nyoman Ayu Suryandari; Ida I Dewa Agung Anggra Arta Putra; Frischa Faradila Arwinda Mongan; Carolus Askikarno Palalangan (Jurnal Abdi Masyarakat Nusantara, 2026)
This community service activity was motivated by the limited use of digital media for marketing and the lack of structured financial recording among the Tenun Ikat Giri Putri MSMEs. In the era of rapid technological development, the ability of MSMEs to adapt is crucial to enhancing the competitiveness of local products. The program aimed to improve participants’ knowledge and skills in digital marketing through social media and to introduce practical digital financial recording applications. The implementation methods included preliminary observation, needs identification, module preparation, direct training, and evaluation. The training covered the use of Instagram and WhatsApp Business as promotional platforms, as well as the introduction of financial applications. The results showed a significant improvement in participants’ ability to use social media for product promotion and to independently manage financial records. Participants also demonstrated strong enthusiasm and commitment to applying the acquired knowledge in their daily business operations. Thus, this activity had a positive impact on strengthening MSMEs’ capacity in both digital marketing and financial management, thereby supporting the sustainability of businesses rooted in local wisdom. In the future, this program is expected to serve as an initial step toward continuous mentoring to achieve MSME independence.